Differentiation of Cell Membranes in Cultures of Embryonic Chick Breast Muscle - Prives, Joav M. (1974)
Three components of differentiated muscle membrane, the acetylcholine receptor, acetylcholinesterase (EC 3.1.1.7; acetylcholine hydrolase), and adenylate cyclase [EC 4.6.1.1; ATP pyrophosphate-lyase (cyclizing)], appear simultaneously during myogenesis in cultures of embryonic chick muscle, after the main period of rapid cell fusion. However, unlike the cytoplasmic proteins of differentiated muscle, the elaboration of these membrane components is unaltered when fusion is blocked by lowering the calcium concentration in the medium. These results suggest that membrane differentiation and cytoplasmic differentiation are regulated independently during muscle development.